Desain Materi Ajar Berbasis Adobe Flash CS6 untuk Meningkatkan Minat Belajar Bahasa Arab Mahasiswa IAIN Ponorogo - Muhammad Nasrullah; Achmad Baihaqi (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
The teaching process is now more focused on interactive media-based learning technology such as CDs, laptops and the Internet, but nowadays many teachers still maintain and use media only based on textbooks, so learning Arabic tends to be boring and student interest is very low. GMI.B students are the average graduates from public schools (SMK and SMA). The purpose of this study was to increase student interest in learning Arabic by designing teaching materials based on Adobe Flash CS6. This study uses the type of research R&D (Research Development) with the ADDIE model, data is collected using observation, interviews, documentation, questionnaires and check lists techniques and then analyzed qualitatively and quantitatively descriptively with (T.test) test. t. Design of teaching materials for Arabic learning based on Adobe Flash CS6 for GMI.B students. The material expert validation stage and media expert validation both gave a score of